Assessment of tumor development and wound healing using endoscopic techniques in mice - Günther, Claudia; Neurath, Markus; Waldner, Maximilian; Neufert, Clemens; Wirtz, Stefan; Becker, Christoph; et al. (Gastroenterology, 2010)
Mouse models of intestinal inflammation and colon cancer are valuable tools to gain insights into the pathogenesis of the corresponding human diseases. Recently, in vivo mouse endoscopy has been developed, allowing not only the high-resolution monitoring and scoring of experimental disease development, but also enables the investigator to perform manipulations, including local injection of reagents or the taking of biopsies for molecular and histopathologic analyses. Chromoendoscopic staining with methylene blue enables visualization of the crypt structure and allows discrimination between inflammatory and neoplastic changes. The development of endoscopic techniques in live mice opened new options for the investigation of disease mechanisms in the gut and for the preclinical testing of potential therapeutic effects of drug candidates. Finally, mouse endoscopy can help to reduce animal numbers needed to gain significant experimental data.